Mechanisms of insulin secretion in malnutrition: modulation by amino acids in rodent models - Machado de Oliveira, Camila Aparecida; Latorraca, Marcia Queiroz; Rostom de Mello, Maria Alice [UNESP]; Carneiro, Everardo Magalhaes (Springer, 2011)
Protein restriction at early stages of life reduces beta-cell volume, number of insulin-containing granules, insulin content and release by pancreatic islets in response to glucose and other secretagogues, abnormalities similar to those seen in type 2 diabetes. Amino acids are capable to directly modulate insulin secretion and/or contribute to the maintenance of beta-cell function, resulting in an improvement of insulin release. Animal models of protein malnutrition have provided important insights into the adaptive mechanisms involved in insulin secretion in malnutrition. In this review, we discuss studies focusing on the modulation of insulin secretion by amino acids, specially leucine and taurine, in rodent models of protein malnutrition. Leucine supplementation increases insulin secretion by pancreatic islets in malnourished mice. This effect is at least in part due to increase in the expression of proteins involved in the secretion process, and the activation of the PI3K/PKB/mTOR pathway seems also to contribute. Mice supplemented with taurine have increased insulin content and secretion as well as increased expression of genes essential for beta-cell functionality. The knowledge of the mechanisms through which amino acids act on pancreatic beta-cells to stimulate insulin secretion is of interest for clinical medicine. It can reveal new targets for the development of drugs toward the treatment of endocrine diseases, in special type 2 diabetes.
Keywords: Malnutrition; Insulin secretion; Amino acids; Leucine; Taurine